Соёлын утгын зэрэгцүүлсэн судалгааны асуудалд: Contrastive studies of cultural connotation - G., Eldev-Ochir (Mongolian Journal of Foreign Languages and Cultures, 2023)
Language shows the cultural characters of a nation and therefore any language of a nation carries the most sophisticated part of culture itself. Language manifests the features of the nation, including national cultual lexicon and national cultural connotation which have close relevance to its national culture. Although National cultural lexicon has national cultural connotation which is the embodiment of the national culture, they are still categorized as language units and national cultural semantics is still semantics. In intercultural communication, words which carry national cultural connotation always become an obstacle in acquisition. People from different cultures should pay much attention to the national cultural connotation of the target language, otherwise misunderstanding is hard to be voided. Hence, when a language learner or culture transmitter is in communication with someone from a totally different background, he should have some knowledge of the national cultural semantics in that language and compare them in details. The better understanding of this, the more successful the communication will be.